Os jogos lúdicos no processo de ensino-aprendizagem da matemática - Segantini, Paulo Henrique (2013)
This work had as its theme the playful in the teaching of mathematics, demonstrating that large are the challenges of teachers in the teaching-learning process of this discipline. The work had its foundation from the history of mathematics that is present in our lives, through the games that encourage interaction and confrontation between different ways of thinking, the role of the teacher, which demonstrates the total interaction with students, the playful, which addresses the development and stimulation of the child's abilities and playful activities, which is the instrument of learning for students and educators. The methodology used is the qualitative research of experimental character that explore the techniques of observation. The target population were students of support rooms. In data collection, questionnaires were used with 10 math teachers who teach at the elementary, middle, and also in support rooms. The students were used experiment with games. Data were analyzed through graphs. In closing remarks after the analyses and conclusions, we see that students need to visualize and experiment with other forms of assimilating contents and the importance of using methods like the playfulness in working in teaching mathematics. Learn the mathematics of playful way is not wasting time and Yes awakening in students a different way of assimilating contents through creativity, interest and to understand the process that leads to the result.